2004
DOI: 10.1124/jpet.103.060780
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Ventricular Proarrhythmia with Selective Opening of the Myocardial Sarcolemmal versus Mitochondrial ATP-Gated Potassium Channel

Abstract: Myocardial ATP-gated potassium channels (K-ATPs) are critical in the intracellular signaling cascade resulting in ischemic preconditioning (IP). Mitochondrial K-ATP channels seem to be responsible for IP, whereas the functions of K-ATP channels in the sarcolemmal membrane are less well understood. The proarrhythmic potential of specific versus nonspecific opening of K-ATP channels has not been investigated. In this study, Langendorff-perfused rabbit hearts were exposed to either pinacidil (1.25 M), a nonselect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 32 publications
2
25
0
3
Order By: Relevance
“…In the present study, pinacidil pretreatment clearly promoted rapid arrhythmias with characteristics of transmural re-entry. This observation supports findings in perfused heart preparations in which pinacidil treatment promoted very rapid ventricular tachyarrhythmias (D'Alonzo et al, 1998;Fischbach et al, 2003Fischbach et al, , 2004.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…In the present study, pinacidil pretreatment clearly promoted rapid arrhythmias with characteristics of transmural re-entry. This observation supports findings in perfused heart preparations in which pinacidil treatment promoted very rapid ventricular tachyarrhythmias (D'Alonzo et al, 1998;Fischbach et al, 2003Fischbach et al, , 2004.…”
supporting
confidence: 80%
“…A study in isolated guinea pig free wall preparations reported that pretreatment with pinacidil before no-flow ischemia improved the recovery of developed tension and abolished severe arrhythmias in reperfusion (Cole et al, 1991). In contrast, other studies found that pinacidil pretreatment promoted arrhythmias induced by global ischemia and reperfusion (D'Alonzo et al, 1998) or hypoxia and re-oxygenation (Fischbach et al, 2003(Fischbach et al, , 2004 in Langendorff-perfused hearts.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…When K ATP channels open during ischaemia, resultant dispersion of refractoriness and slowing of conduction could predispose to reentrant arrhythmias; by preventing these effects, K ATP channel blockade could be anti-arrhythmic and protective. In fact, some studies have indicated that K ATP channel blockers reduce the propensity for ischaemic arrhythmias [12,13], while K ATP channel openers facilitate induction of ventricular fibrillation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The selective benzopyran derivate, BMS 191095, elicited both antinecrotic (Neckar et al 2002) and antiarrhythmic (Fischbach et al 2004) protection in the rodent heart subjected to I/R injury, being recognized as an useful tool for basic research (Grover and Atwal 2002). Accordingly, further studies addressing the role of novel benzopyran analogues in preventing the deleterious effects of reperfusion injury are warranted.…”
Section: Mitochondrial H 2 O 2 Productionmentioning
confidence: 99%